The Twenty-Second Annual Conference of the AMSS: 28 Rabi al Akhir-1 Jumada- al Awwal 1414/15-17 October 1993 International Institute of Islamic Thought, Herndon, Virginia (American Journal of Islam and Society, 1994)
The Twenty-Second Annual Conference of the Association of MuslimSocial Scientists (AMSS) was jointly organized by the Intemational Instituteof Islamic Thought (IIIT) and the AMSS and was held at the IIITpremises in Hemdon, VA. The open-theme conference featured eighteenpanels organized into fourtem sessions.The opening session consisted of the welcoming address by DilnawazSiddiqui, President (Clarion University of Pennsylvania, Clarion, PA), remarksby Mushtaqur Rahman, Conference Chairman (University of Iowa,Ames, IA), and the inaugural address of Taha al 'Alwani (President,IIIT). The second session, "Islamic Philosophy and Compamtive Approaches,"was chaired by Ja'afar Sheikh Idris (Institute of Islamic andArabic Sciences, Fairfax, VA). Presentations included "Islamic Theory ofKnowledge: A Reapptaisal" by Sirajul Husain (Islamic Research and DevelopmentCouncil, Cleveland, OH), "Islamization of the Creative Imaginationand Its Ramifications in the Visual Arts of Islam" by Halide A.Salam (Radford University, Radford, VA), and "The Concept of Free Willin the Comments of al Ash'ari, al Hilli, and Taftazani" by Anne E.Francisse (Seattle, WA).The third session had two concurrent panels: "Concept of Shzird andDemocracy in Islam," chaited by Mumtaz Ahmad (Hampton University,Hampton, VA) and "Culture and Communication," chaired by Ali Ramadan(IIIT). The first panel comprised Aziza a1 Hibri (University of Richmond,Richmond VA) and Ja'afar Shaikh Idris. Al Hibri pointed out thatshura (mutual consultation) is part of Islamic constitutional theory and reflectsthe divine dimension of an Islamic political framework-while democracyis one process of shzirti reflecting the human will in the politicalplane. Also featured was Hamid al-Ghazali (Islamic Center of Lawrence,Lawrence, MO), who gave a special report on the removal of an unjustleader from an Islamic institution that had been presented to the CircuitCourt of Jackson County, Missouri.The culture and communication panel had three presentors. ShamfRahman (Northern State Univedty, Aberdeen, SD) spoke on media typesand Muslim culture vis-8-vis Pakistani films and videos. Hussein Abiva(Chicago, IL) dealt with the role and importance of Sufi orders in Balkan ...